Catch history and status of the harbour seal (Phoca vitulina) in Greenland - Rosving-Asvid, Aqqalu (NAMMCO Scientific Publications, 2010)
The number of harbour seals (Phoca vitulina) in West Greenland declined rapidly after the 1950s and the seals have now abandoned their traditional haulout locations along the Greenland west coast. However, in recent years, a previously undetected group of about 60-100 harbour seals has been observed approximately 80 km upstream in a large river, and some traditional hauloutlocations are still in use near the south-eastern tip of Greenland. A small number of harbour seals is caught annually far from any of these locations, indicating that other groups might live unnoticed. Catch statistics provide the best evidence of the presence and locations of these remnant harbour seals. Therefore efforts were made to validate the recent catch statistics and to describe the catch history for the past 60 years. The catch statistics were also used to estimate plausibleranges of past and present numbers of harbour seals based on the assumption that hunting has caused the observed decline. The total number of harbour seals in Greenland according to these estimates was about 3,000 in 1950 and fewer than 1,000 in 2007. The number of harbour seals caught in the southernmost part of Greenland has, unlike in the rest of Greenland, increased significantly in some of the recent years. This change seems to be related to changes in the amount of drift ice. Drift ice reduces the frequency of contact between hunters and harbour seals in South Greenland and above normal quantities of drift ice from the mid 1960s to the mid 1980s probably allowed these seals to increase in numbers. Record low inflow of drift ice in some of the recent years, however, has resulted in record high catches, which likely have reduced the seals again. The remaining harbour seals in Greenland are few and without protection these sealsare potentially in danger of extinction.